Penggunaan Mind Mapping Terhadap Pemahaman Mitigasi Bencana - Kurniawan, Trubus; Suwarno, Suwarno (Proceedings Series on Social Sciences & Humanities, 2022)
Learning Disaster Mitigation Materials needs to be given to students, so that students have an understanding of the importance of disaster mitigation because Indonesia is a disaster laboratory where almost all disasters have the potential to occur in Indonesia. A good learning process must contain interactive, fun, challenging, motivating aspects and provide more space for students to be able to develop creativity and independence, according to students’ talents and interests. Interesting learning media is very necessary for junior high school students, one of the developments in the learning model that is currently still new is the learning model using Mid Mapping. Understanding the concept of disaster mitigation through the Mind Mapping learning model is expected to be a fun and easy learning alternative for students, so that students understand the basics of disaster mitigation. The purpose of this paper is to provide an overview of the understanding of the concept of disaster mitigation for class VII students before and after learning by using Mind Mapping media and introducing the use of Mind Mapping learning media to students.